Hubungan Perilaku Sehat Dengan Sikap Penggunaan Suplemen Vitamin C di Kota Denpasar - ASRINI, NI PUTU MITHA (Bali International Scientific Forum, 2021)
ABSTRACT THE RELATIONSHIP BETWEEN HEALTHY BEHAVIOUR WITH THE ATTITUDE OF USING VITAMIN C SUPPLEMENTS IN DENPASAR CITY , , Clinical Pharmacy Study Program Faculty of Health Sciences, University of Bali International. Email: mitha.asrini@gmail.com Background: Health is a right for everyone, whether physically, mentally, spiritually or socioeconomically. Healthy behavior is used as a benchmark in achievement to improve health coverage. Healthy behavior is one of the important roles and positively influences realizing public health status. To support people's healthy behavior, taking vitamin C supplements is needed to strengthen immunity. Vitamin C supplements are used as maintenance of endurance in supporting health behaviors to improve health behaviors. Purpose: This study aims to find out the relationship of healthy behavior with the attitude of using vitamin C supplements in Denpasar City. Method: The research design used in this study is descriptive with a cross sectional research design. The number of samples taken was 412 respondents by purposive sampling. Measurements are carried out using questionnaires. The data analysis technique used in this study is Rank Spearman. Result: Based on the results of the study, 54.1% of people of Denpasar City have positive healthy behavior with the attitude of using vitamin C supplements with a positive category of 51.9%. Conclusion: There is a significant relationship between healthy behavior and attitudes towards the use of vitamin C supplements in Denpasar City, with a correlation of 0,582, which is a positive relationship.